Plasmon resonance tuning using DNA origami actuation1. Issue 23 (21st March 2015) - Piantanida, Luca; Naumenko, Denys; Torelli, Emanuela; Marini, Monica; Bauer, Dennis M.; Fruk, Ljiljana; Firrao, Giuseppe; Lazzarino, Marco
<x xml:space="preserve">Abstract</x> A strategy for an innovative, continuous and reversible LSPR tuning using DNA origami actuation to modulate the nanometric separation of two gold nanoparticles has been developed.